2023
DOI: 10.1177/20503121231170743
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cyanoacrylate glue in the fixation of midline catheters and peripherally inserted central catheters in hospitalised adult patients: Randomised clinical trial (CIANO-ETI)

Abstract: Objective: The objective of the study was to assess the efficacy of the use of cyanoacrylate glue (CAG) as a means of securing midline catheters and peripherally inserted central catheters with the modified micro-Seldinger technique in adult hospitalised patients. Methods: Randomised clinical trial with two groups (1:1): control and intervention. The control group received a securement method with a sutureless device plus transparent dressing and the intervention group received the same securement method plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In general, placement of catheters in vessels with low blood flow increases the risk of thrombosis; in both cases in our study group, catheter migration may have contributed to the thrombosis. Previous studies have shown that the use of CG was effective in reducing bleeding at the puncture site and controlling infection rather than immobilizing the catheter 14–16 . Our study using chest radiographs showed that the use of CG also inhibited catheter tip migration within the body.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In general, placement of catheters in vessels with low blood flow increases the risk of thrombosis; in both cases in our study group, catheter migration may have contributed to the thrombosis. Previous studies have shown that the use of CG was effective in reducing bleeding at the puncture site and controlling infection rather than immobilizing the catheter 14–16 . Our study using chest radiographs showed that the use of CG also inhibited catheter tip migration within the body.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have shown that the use of CG was effective in reducing bleeding at the puncture site and controlling infection rather than immobilizing the catheter. [14][15][16] Our study using chest radiographs showed that the use of CG also inhibited catheter tip migration within the body. Because arrhythmias were not monitored, their incidence rate could not be evaluated.…”
Section: Catheter Tip Migration and Venous Thrombosismentioning
confidence: 82%
See 2 more Smart Citations
“…In a sample of patients, Arista TM AH powder was applied at the site of anastomosis instead of glue, and a comparison of the two devices was carried out to test their stability and effectiveness at that site of action (Figure 3B). The procedure for stabilization and fixation of the PICCs (peripherally inserted central catheters) took place in the angiography room after identification by ultrasound of the endovascular access site and exclusion of in situ thrombosis [37,38] (Figure 4). If the identified site was affected by venous thrombosis, the other arm was used.…”
Section: Data Collections and Proceduresmentioning
confidence: 99%